(untitled) (Bon Voyage, 2019)
This paper analyzes holi dance entitled Abiraya holi in Pradeep Rimal directed Newari movie Silu (1987), the first ever ethnic movie made in Nepal, as a seasonal folklore that signifies the arrival of the New Year. Holi provides a context of social interaction for young men and to present themselves in front of the elders in among Newar community in Kathmandu Valley. My inquiry into the Newari culture through the movie is how holi celebration marks the beginning of new life for a newly married couple. As holi is a harbinger of New Year a giving them chance to familiarize with new ones. Not only that, it further examines that celebration of holi at the dawn of New Year bring families, relatives and young people from different clans together. Thus, holi becomes a basis for strengthening the relationship between protagonists in the movie and people in the society. In order to highlight holi dance as popular folklore among Newar community and it as an enactment of sharing a cultural tradition of Newars in Silu, this paper brings cultural studies on board to study the intersection of holi, New Year and newly married couples.